Assessing the Construct Validity and Reliability of the Modified Adolescent Parenting Attitude Four Factor Questionnaire with Rasch Measurement Model - Woo, Vincent Ming-Wei; Yeo, Kee Jiar (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to conduct a validity and reliability test on the modified version of adolescent parenting attitude four factor questionnaire (APA-FFQ) with rasch measurement model (RMM). The adapted instrument consisted of 40 items based on 4 constructs namely authoritarian, authoritative, permissive and uninvolved parenting style. Some items in the instrument have been rephrased to improve the clarity. Besides, the researcher also created different columns for each item to capture the type of maternal and paternal parenting style. Based on the sample size of 70 adolescents from one of the private higher education institution in Malaysia, the analysis revealed that all items in the modified version of APA-FFQ fit the model as the value of MNSQ was fell in between the acceptable range of 0.50 to 1.50 with positive PTMEA value. The dimensionality analysis also revealed that all items were measured what it supposed to measure and possessed a strong unidimensionality. Furthermore, the separation and reliability index also showed that all respondents and items are consistent in measuring the same construct with different items. Thus, the study concluded that such instrument can be adapted in the Malaysian educational context.